(untitled) (Journal of International Studies, 2020)
President Donal Trump announced the U.S. withdrawal from the 2015 Paris Agreement, and stated that the withdrawal was mainly to protect its national interests. The U.S. economic ambitions, the China factor and the intricacies of U.S domestic politics had played a major role in deciding the U.S. position on the Paris Agreement and the Kyoto Protocol of 1997. There are some who are sceptical on whether the Paris Agreement would successfully achieve its expected outcomes in the absence of U.S. participation. The objective of this study is to examine the factors that have discouraged the U.S. to partake in the international climate change agreements. An analytical framework was employed for this study that examines the insights and conceptions from the textual data, based on realism. The study concludes that the U.S. outlook on climate change had more or less adhered to the realist stance, even though realism is considered a theoretical approach with significant drawbacks, particularly when dealing with issues of climate change. Nonetheless, this study also asserts that there is a need for deeper engagement between the U.S. and the participants of the Paris Agreement to effectively tackle the issues of climate change at this moment.